Pareto-Improving Minimum Corporate Taxation - Hebous, Shafik (IMF Working Papers; Working Paper, 2021)
The recent international agreement on a minimum effective corporate tax rate marks a profound change in global tax arrangements. The appropriate level of that minimum, however, has been, and remains, extremely contentious. This paper explores the strategic responses to a minimum tax, which-the policy objective being to change the rules of tax competition game---are critical for assessing the design and welfare impact of, and prospects for, this fundamental policy innovation. Analysis and calibration plausibly suggest sizable scope for minima that are Pareto-improving, benefiting low as well as high tax countries, over the uncoordinated equilibrium.